The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13287-020-01943-w
|View full text |Cite
|
Sign up to set email alerts
|

UBA2 activates Wnt/β-catenin signaling pathway during protection of R28 retinal precursor cells from hypoxia by extracellular vesicles derived from placental mesenchymal stem cells

Abstract: Background Stem cell transplantation has been proposed as an alternative treatment for intractable optic nerve disorders characterized by irrecoverable loss of cells. Mesenchymal stem cells, with varying tissue regeneration and recovery capabilities, are being considered for potential cell therapies. To overcome the limitations of cell therapy, we isolated exosomes from human placenta-derived mesenchymal stem cells (hPMSCs) and investigated their therapeutic effects in R28 cells (retinal precur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…1c ). Western blot analysis demonstrated that the exosome surface proteins CD63, CD9 and TSG101 42 , 43 were expressed in the 2D- and 3D-exos, but the cytosolic marker GM130 was absent in the 2D- and 3D-exos (Fig. 1d ).…”
Section: Resultsmentioning
confidence: 96%
“…1c ). Western blot analysis demonstrated that the exosome surface proteins CD63, CD9 and TSG101 42 , 43 were expressed in the 2D- and 3D-exos, but the cytosolic marker GM130 was absent in the 2D- and 3D-exos (Fig. 1d ).…”
Section: Resultsmentioning
confidence: 96%
“…Previously, we demonstrated the therapeutic efficacy of exosomes from MSCs. They enhanced the neuroprotective and neurorecovery abilities of in vitro models [29]. UBA2 expression is increased in a time-dependent manner in response to hypoxia, and is upregulated in the exosome [1].…”
Section: Discussionmentioning
confidence: 95%
“…If samples containing proteins are culture media, exosomes, or body fluids such as serum, plasma, saliva, tears, nasal fluids, urine, or aqueous humor, they do not require lysis pretreatment. In these cases, an appropriate amount of buffer is added to favor subsequent enzymatic digestion steps [63,64]. If samples are cells, a lysis step is applied to break the cell membrane.…”
Section: Sampling and Sample Pretreatmentmentioning
confidence: 99%